2010
DOI: 10.3389/neuro.08.045.2009
|View full text |Cite
|
Sign up to set email alerts
|

Of lion manes and human beards: some unusual effects of the interaction between aggression and sociality

Abstract: The function of manes in lions has been a topic of scientific interest since Darwin (1871) suggested that it provides protection in intraspecific fights. Recent experimental studies on wild lions have emphasized the role of female selection, but analyses of specific attack behaviors and targets, and the social consequences of manelessness for lions living in very hot climates suggest that male manes may indeed mitigate the outcomes of intraspecific male attack and thus serve a permissive function for multi-mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…In MMA, the majority of serious injuries occur on the face, particularly the jaw and cheek bones (Lystad et al, 2014), which are the regions where beard growth is most profuse . Blanchard (2009) suggested that the human beard functions like the mane of the male lion in providing protection to the face and neck during fights. We found no evidence that bearded fighters succumb to fewer knockouts than clean-shaven fighters and therefore conclude that facial hair does not provide any protective advantage during male-male contest competition.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…In MMA, the majority of serious injuries occur on the face, particularly the jaw and cheek bones (Lystad et al, 2014), which are the regions where beard growth is most profuse . Blanchard (2009) suggested that the human beard functions like the mane of the male lion in providing protection to the face and neck during fights. We found no evidence that bearded fighters succumb to fewer knockouts than clean-shaven fighters and therefore conclude that facial hair does not provide any protective advantage during male-male contest competition.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The UFC provides a unique opportunity to test whether beards provide any advantage to fighters or reflect a fighter's performance. While most sports that involve fights, including groups that sanction boxing and wrestling, restrict the growth of facial hair owing to views that it enhances protection against blows (Blanchard, 2009), this restriction does not apply in the UFC. Although beards cannot enhance fighting ability directly, there are two main hypotheses that suggest evolutionary advantages for facial hair during intra-sexual contests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dark-maned males enjoyed greater survival and reproductive success; thus, the lion's mane appears to be an honest indicator of being able to take the heat, rather than as a shield to protect the head and neck against wounding (West et al, 2006). Amusingly, our work inspired several investigations into the function of the male beard in humans (Blanchard, 2010;Dixson and Vasey, 2012).…”
Section: The Basics Of Lion Biologymentioning
confidence: 78%
“…Blanchard, 2010; Estes, 1991). However, the laboratory-based study of sociality and species-typical social patterns has generally lagged behind that of more easily manipulated systems such as defense, ingestion, or sexual behavior.…”
Section: An Animal Model Of Autismmentioning
confidence: 99%